Compensating for Sexual Identity: How LGB and Heterosexual Australian Police Officers Perceive Policing of LGBTIQ+ People - Miles-Johnson, Toby (Journal of contemporary criminal justice, 2020)
Police officers are highly criticized for their differential policing of people categorized by identity. One such group who has experienced differential policing is the lesbian, gay, bisexual, transgender, intersex, and queer (LGBTIQ+) community. Contributing new knowledge to the extant policing literature regarding intersectional identities of Australian police officers and perceptions of policing, this research applies Social Identity Theory to understand differences between lesbian, gay, bisexual, and transgender and heterosexual self-identified general-duties police officers (N = 349) and policing of LGBTIQ+ people. Using an online survey, results suggest the sexual identity of a general-duties police officer does shape perceptions of policing of LGBTIQ+ people. Furthermore, there are distinct differences in the way heterosexual and lesbian, gay, and bisexual (LGB) self-identified officers perceive police engagement with LGBTIQ+ people, with LGB and heterosexual self-identified officers equally compensating for their sexual identity in terms of policing LGBTIQ+ people and distancing themselves from the LGBTIQ+ community.